Peningkatan Aktivitas dan Hasil Belajar Peserta Didik Tema Tugasku Sehari-Hari Materi Uang Melalui Model Discovery Learning dengan Metode Pemberian Tugas di Kelas II SD N 02 Gurun - Nasmai Nasmai (Journal on Education, 2022)
This study aims to see and analyze the Increase in Student Activities and Learning Outcomes the Theme of My Daily Tasks Material Money Through the Discovery Learning Model with the Assignment Method in Class II SDN 02 Gurun. This research was carried out using the Classroom Action Research method which consisted of two cycles, where each cycle consisted of: planning, action, observation and reflection. It is carried out from August to October 2021. Data is processed in each cycle and then analyzed using percentages. The results obtained from this study are the discovery learning model, the assignment method can improve student learning outcomes. This is evident from the increase in the learning activities of pre-cycle students = 63%, cycle I = 75%, and cycle II = 88%. For teacher activity in pre-cycle = 61%, cycle I = 72%, and cycle II = 92%, for mastery learning knowledge increased from pre-cycle 65.29 = 47%, cycle I 71.17 = 59%, and cycle II 80 ,00 = 82% For mastery learning skills, namely pre-cycle, pre-cycle 68.23 = 59%, cycle I 74.11 = 65% and cycle II 80.58 = 82%. The conclusion obtained from this research is that the use of the discovery learning model of the assignment method can increase the activities and learning outcomes of students.